(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Genetic disorders are one of the major childhood health problems. Treatment and rehabilitation of children with genetic disorders are costly and complete recovery is usually impossible. Genetic disorders are far more common than is widely appreciated and represent only the tip of the iceberg. Consanguineous marriage increases the risk of mutated autosomal recessive gene expression and consequently increases the risk of inheriting genetic disorders among the offspring. The probability of inheriting genetic disorders depends on the closeness of the relationship between the parents. That’s why considerable attention has been attracted towards the consanguineous marriage as a causative factor of the genetic disorders. It was found that the rate of consanguinity is very high among the Muslim countries. Very limited data are available regarding the rate of consanguinity and prevalence of genetic disorders related to consanguinity in Bangladesh. Bangladesh has a lot of achievements in the health sector but still, sufficient initiative have not been taken to control the genetic disorders by informing, motivating and discouraging people in consanguineous marriage. Awareness of the people with premarital and prenatal screening is very important to reduce the incidence of genetic disorders. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 59-63